Youth report of healthcare transition counseling and autonomy support from their rheumatologist - Wells Courtney Kellerman; McMorris Barbara J; Horvath Keith J; Garwick Ann W; Scal Peter B (BMC, 2012)
Abstract Background To increase understanding of the healthcare transition (HCT) process for young people living with Juvenile Idopathic Arthritis (JIA) by examining: 1) the extent to which youth report discussing HCT topics with their rheumatologist and 2) the association between youth perceptions of autonomy support from their rheumatologist and HCT discussions. Methods Data are from an online survey of youth in the United States with rheumatologic conditions (n= 134). HCT discussion was measured by 4 questions from the National Survey of Children with Special Health Care Needs. Youth perception of autonomy support was measured using a validated 6-item scale. Results One third of the youth (33.7%) reported talking to their rheumatologist about transferring to adult medicine. Less than half (40.8%) of respondents talked with their rheumatologist about adult healthcare needs, and less than a quarter (22.0%) discussed acquiring health insurance as an adult. Nearly two-thirds of respondents (62.7%) reported that their rheumatologist usually/always encourages self-care responsibility. Multivariate analyses revealed significant associations between rheumatologist support for youth autonomy and HCT counseling. Conclusion The low frequency of HCT counseling reported indicates a continuing need to increase awareness among rheumatologist in the USA. The strong associations between rheumatologist's support for youth autonomy and HCT counseling suggest that developmentally "in-tune" providers may deliver the best guidance about transition planning for youth living with arthritis.